#### Answer

$d_1=tV + d_2$

#### Work Step by Step

Multiply $t$ to both sides to find:
$t \cdot V = t \cdot \dfrac{d_1-d_2}{t}
\\tV = d_1-d_2$
Add $d_2$ to both sides to find:
$tV + d_2 = d_1-d_2+d_2
\\tV + d_2 = d_1
\\d_1=tV + d_2$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$d_1=tV + d_2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.